2019
DOI: 10.3889/oamjms.2019.260
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Nursing Care Model Based on Culture to Improve the Care of Malnourished Madurese Children in Indonesia

Abstract: AIM: The purpose of this study is to analyse the usage of nursing care model based on culture to improve parenting practices related to malnutrition among Madurese children. METHODS: This study uses a quasi-experimental design and a purposive sample of 102 respondents from families with toddlers who suffered from nutritional deficiency. The sample consisted of an intervention group (n = 51) and a control group (n = 51). Data were collected using a questionnaire and weight measurement. RESULTS: A t-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In the end, the gender ideological context attaches the position of women as companions to husbands, household regulators and the primary caregivers of children, thereby weakening the bargaining position of wives towards husbands in making decisions in the household. This condition ultimately makes women not economically independent so that it can have consequences on access to health services during pregnancy and childbirth 12,13 . This situation is still very strong, especially in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…In the end, the gender ideological context attaches the position of women as companions to husbands, household regulators and the primary caregivers of children, thereby weakening the bargaining position of wives towards husbands in making decisions in the household. This condition ultimately makes women not economically independent so that it can have consequences on access to health services during pregnancy and childbirth 12,13 . This situation is still very strong, especially in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…However, important interventions should be undertaken to increase awareness and sensitivity when working with diverse patients [6]. A study by Hidayat and Musrifatul in 2019 found that the culture-based nursing care model is a culture-based approach model that plays an important role in overcoming children's health problems in the community, especially when cultural factors are conflicting with healthy principles [7].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Russell Salvador in 2018 found that HCPs are very culturally competent, especially in changing aspects of behavior [6], [7]. The role of older mothers who are close to pregnant women may be relevant when conveying information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parenting entails making sure that a family gets enough high-quality food and nutrition, especially the children, who are not able to fend for themselves. Observing proper feeding patterns also helps to improve the nutritional status of children [21], [22].…”
Section: Discussionmentioning
confidence: 99%